Kedudukan dan Kekuatan Hukum Putusan Pandi serta Penerapan Online Dispute Resolution (ODR) dalam Sengketa Nama Domain - Misyela, Kezia; Henry Arianto (DOKTRINA: JOURNAL OF LAW, 2026)
The rapid growth of information technology has led to a significant rise in the use of domain names as strategic digital identities for individuals, businesses, and institutions. This development increases the likelihood of disputes, particularly when domain names are registered or used without proper rights or in bad faith. This study examines the legal standing and binding force of decisions issued by the Indonesian Internet Domain Name Registry (PANDI) and analyzes the procedural model of dispute resolution through the Domain Name Dispute Resolution Process (PPND) within Indonesia’s legal framework. Using a normative juridical approach, this research reviews relevant legislation, regulatory instruments, and academic literature on domain name governance and Online Dispute Resolution (ODR). The findings indicate that PANDI’s decisions are binding within the non-litigation system and derive their authority from statutory mandates, while still allowing parties to challenge the outcome before the Commercial Court. Furthermore, the PPND mechanism demonstrates efficiency and adaptability, embodying the principles of responsive law and Alternative Dispute Resolution (ADR). Consequently, PPND serves as an essential mechanism for ensuring legal certainty and maintaining the integrity of Indonesia’s digital landscape.